Endovascular Aspiration Thrombectomy of the Superior Mesenteric Artery for Treatment of Acute Mesenteric Ischemia: Results From the ENDO-SMA2MI Registry - Mario D’Oria; Sandro Lepidi; Paolo Spath; Mauro Gargiulo; Ciro Ferrer; Gioele Simonte; Stefano Gennai; Francesco Giurazza; Anna Maria Ierardi; Diego Visconti; Reinhold Perkmann; Raffaello Bellosta; et al. (Journal of Endovascular Therapy, 2026)
Background/Objective. Acute mesenteric ischaemia (AMI) is a multidisciplinary emergency, requiring the involvement of different medical specialties for successful management. Endovascular aspiration thrombectomy (EAT) has entered the field leading to the possibility of treating acute arterial occlusions with a minimally invasive approach. The aim of the study was to provide contemporary data on results after use of EAT in AMI patients. Methods. The study was a retrospective, observational, multicentre study conducted in 10 Italian centres. Patients with AMI, undergoing EAT of the superior mesenteric artery (SMA) with the Penumbra Indigo system (Penumbra Inc., Alameda, CA, USA) from January 1, 2020 to December 31, 2024 were enrolled. Technical success and mortality were the primary outcomes. Secondary outcomes included perioperative complications and length of stay in the hospital and intensive care unit (ICU). Results. Forty-eight consecutive AMI patients undergoing EAT were enrolled in the study. The median age of the study population was 80 years (interquartile range [IQR] = 68-86), and 52% were male. The median time from emergency acceptance up to referral for definitive treatment was 1 hour (IQR = 1-5), with 77% of patients presenting to the hospital less than 6 hours from onset of symptoms. Overall, 29 patients (60%) received only EAT at presentation, whereas 19 patients (39%) received a combined general surgical procedure at the same time of endovascular intervention. Technical success of EAT was achieved in 44 cases (92%). Thirty-one patients (64%) required ICU stay, with a median duration of 1.5 days. Severe postoperative complications (i.e. Clavien-Dindo scale >3) occurred in 28 patients (58%), and the average duration of hospital stay was 10 days. The overall rate of 90-day mortality was 46% (n = 22); of these, 19 deaths occurred in the first 30 days and 3 additional events occurred between 30 and 60 days after index presentation. On multivariable analysis, a procedure longer than 90 minutes (odds ratio [OR] 6.3; 95% confidence interval [CI], 1.0-37.2; P = .041) and Clavien-Dindo score greater than 3 (OR 19.5; 95% CI, 3.2-115.5; P =